2016
DOI: 10.1177/0284185116647211
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prior mammograms on combined reading of digital mammography and digital breast tomosynthesis

Abstract: Background Although digital breast tomosynthesis (DBT) is an emerging technique yielding higher sensitivity and specificity compared to digital mammography (DM) alone, relative contribution of prior mammograms on the interpretation of DBT combined with DM has not been investigated. Purpose To retrospectively compare the diagnostic performances of DM, DM + DBT, and DM + DBT with prior mammograms. Material and Methods Three breast radiologists independently reviewed images of 116 patients with 24 cancers in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…1 ). Finally, 20 articles with 44513 patients and 58388 lesions fulfilled the eligibility criteria [ 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 ]. Table 1 presents the characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). Finally, 20 articles with 44513 patients and 58388 lesions fulfilled the eligibility criteria [ 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 ]. Table 1 presents the characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Of these studies, 50% were conducted in Asian countries [ 18 19 20 23 25 27 29 31 32 33 ], and there were four prospective studies [ 18 19 32 33 ]. Five studies had patients with breast density ≥ 2 or b according to American College of Radiology (ACR) [ 28 29 30 31 34 ], nine studies consecutively sampled participants [ 18 21 22 24 25 26 32 34 35 ], and 13 studies performed a per-lesion analysis [ 18 19 20 21 22 23 25 26 28 29 31 32 33 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies show a significantly higher specificity with the addition of DBT to DM in screening 7,36,37,42,46,48,50,51. Other studies, however, concluded that there was a non-statistically significant increase 16,39,41. It should be noted that the three latter studies have in common a relatively small number of participants (100–200 women).…”
Section: Results: Studies On the Optimal Use Of Digital Breast Tomosymentioning
confidence: 99%
“…Similarly, the usage of prior mammograms might have an impact on the screening capabilities of a system. As shown by Kim et al,41 prior mammograms can affect the specificity of the imaging systems. In addition, as discussed above, patient specific background might affect the optimum usage of an imaging system and this has been recently assessed in a few studies 25,35.…”
Section: Considerations For Dbt Implementationmentioning
confidence: 99%
“…Recent studies have shown that tomosynthesis is better than mammography in cancer detection and lesion characterization . It can be predicted that these advantages would also contribute to specimen imaging.…”
Section: Discussionmentioning
confidence: 99%